The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1097/00004032-200206000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Skin Dose With Radiochromic Dosimetry Film in the Cardiac Catheterization Laboratory

Abstract: A new radiochromic dosimetry film was tested to determine its potential for patient skin dose monitoring in a fluoroscopically intensive environment such as the cardiac catheterization laboratory. The dose, time, energy, dose fractionation, dose rate, and sheet to sheet uniformity response were tested. All tests support the conclusion that this is a simple, noninvasive, retrospective method to identify skin regions at risk from high x-ray doses. The consistency and accuracy of dose measurements allow for an es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 10 publications
3
39
0
Order By: Relevance
“…The performance claimed by the manufacturer may be overestimated, however (i.e. doses below 0.2 Gy may be less reliable [9,24]). Indeed, when the X-ray beam projection is far away from the vertical position (LOA 90 u , for instance, or close to it), the primary beam cannot intercept the film.…”
Section: Discussionmentioning
confidence: 99%
“…The performance claimed by the manufacturer may be overestimated, however (i.e. doses below 0.2 Gy may be less reliable [9,24]). Indeed, when the X-ray beam projection is far away from the vertical position (LOA 90 u , for instance, or close to it), the primary beam cannot intercept the film.…”
Section: Discussionmentioning
confidence: 99%
“…The films were scanned with a Canon MX310 scanner (75 DPI, color mode) 24 h after the exposure, and the red channel of the image was used as recommended by Giles and Murphy. 19 All films were exposed and scanned in the same orientation, so as to minimize the error due to the polarization effect of the film. 20,21 A calibration curve was acquired by plotting the dose versus the respective red channel values 22 and fitting the data with a fourth degree polynomial equation which had an r 2 value of 0.997 48.…”
Section: H2 Comparison With Gafchromic Filmmentioning
confidence: 99%
“…Giles and Murphy 8 demonstrated that the optical density of an exposed GafChromic XR film became fairly stabilized by 24 h post exposure. They monitored the changes in the optical density to about 12 days post‐exposure.…”
Section: Discussionmentioning
confidence: 99%
“…– 3 Specifically, the GafChromic dosimetry media (International Specialty Products, Wayne, NJ) has been very useful for the mapping of dose distributions in radiation therapy 4 7 Increasing concern for the potentially high radiation dose in interventional radiological procedures has led to the use of radiochromic films in this imaging modality 8 . The GafChromic XR Type R Dosimetry film (International Specialty Products, Wayne, NJ) has recently been introduced to meet this need.…”
Section: Introductionmentioning
confidence: 99%